2021
DOI: 10.1200/jco.2021.39.15_suppl.3579
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA and circumferential resection margin as key prognostic indicators for survival in rectal cancer.

Abstract: 3579 Background: Recurrence of colorectal cancer has been linked to the presence of epigenetic circulating tumour DNA (ctDNA) in patient plasma after surgery. The prognostic significance of ctDNA prior to treatment remains unknown. This study investigated the correlation between pre-treatment ctDNA and current radiological (MRI) prognostic markers in patients with rectal cancer. Methods: Forty-two patients with rectal cancer were enrolled, with all having staging MRI prior to treatment. Plasma was taken for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Clinically, it is generally believed that primary tumor, metastases, and circulating tumor cells are the main sources of ctDNA [18,19]. Some studies have also found that the infiltration and metastasis of cancer cells can lead to an increase in the level of ctDNA in the body [20,21], suggesting that it may be related to the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, it is generally believed that primary tumor, metastases, and circulating tumor cells are the main sources of ctDNA [18,19]. Some studies have also found that the infiltration and metastasis of cancer cells can lead to an increase in the level of ctDNA in the body [20,21], suggesting that it may be related to the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it is generally believed that primary tumor, metastases, and circulating tumor cells are the main sources of ctDNA [ 18 , 19 ]. Some studies have also found that the infiltration and metastasis of cancer cells can lead to an increase in the level of ctDNA in the body [ 20 , 21 ], suggesting that it may be related to the prognosis of patients. The results of this study showed that the plasma ctDNA level of the death group was higher than that of the survival group, and the survival rate of the high (ctDNA) expression group was lower than that of the low expression group, indicating that the higher the plasma ctDNA level was, the higher the risk of poor prognosis would be.…”
Section: Discussionmentioning
confidence: 99%
“…Correlative studies evaluating patients with LARC have been concordant in showing association between ctDNA levels and clinical response to either chemoradiotherapy (CRT) or surgery [ 37 , 38 , 39 , 40 , 41 , 42 ]. Additionally, four studies demonstrated correlation between ctDNA levels and tumor regression grade (TRG) score in MRI after CRT [ 38 , 39 , 42 , 43 ], and another one showed association between involvement of circumferential resection margin and detection of ctDNA by a methylation-based assay [ 44 ]. However, studies have showed discordant results in demonstrating the value of ctDNA for predicting pCR [ 40 , 41 , 45 , 46 ].…”
Section: Mrd In Rectal Cancermentioning
confidence: 99%